A novel architecture for achieving high drug loading in amorphous spray dried dispersion tablets - Deanna M. Mudie; Stephanie Buchanan; Aaron M. Stewart; Adam Smith; Kimberly B. Shepard; Nishant Biswas; Derrick Marshall; Alyssa Ekdahl; Amanda Pluntze; Christopher D. Craig; Michael M. Morgen; John M. Baumann; et al. (Elsevier, 2020)
Although Amorphous Solid Dispersions (ASDs) effectively increase bioavailability, tablet mass can be high due to the large fraction of excipients needed to stabilize the amorphous drug in the solid state, extend drug supersaturation in solution and achieve robust manufacturability. The aim of this work was to reduce tablet mass of an ASD tablet comprising a low glass transition temperature (Tg), rapidly crystallizing drug without compromising these key attributes.In this approach, erlotinib (Tg = 42 °C, Tm/Tg = 1.4 K/K) was spray dried with the high Tg polymer poly(methyl methacrylate-co-methacrylic acid) (Eudragit® L100, Evonik) (Tg = 187 °C) to facilitate high drug loading while maintaining physical stability. Hydroxypropyl methylcellulose acetate succinate (HPMCAS) (AQOAT® HF, Shin-Etsu) was granulated with the ASD to extend supersaturation in solution. For comparison, a benchmark ASD was spray dried at a lower drug loading with HPMCAS-H (Tg = 119 °C).This High Loaded Dosage Form (HLDF) approach reduced tablet mass by 40%, demonstrated similar physical stability and in vitro performance as the benchmark and exhibited excellent downstream manufacturability. Strategically combining two different polymers in a tablet to maintain physical stability and sustain supersaturation in solution can decrease tablet mass of some low Tg, rapidly crystallizing amorphous drugs.